ANALYSIS OF SOURCES IN THE 16TH CENTURY HISTORY OF THE FERGANA VALLEY - Abdurashid Abdurasulovich Nishonov (European Journal of Humanities and Educational Advancements, 2022)
The article analyzes the sources on the history of the Fergana Valley in the sixteenth century, and the lack and scattering of information about the Fergana Valley in the historical sources of the Sheibani period is critical of the available data.